Persepsi Pengusaha Atau Pemberi Kerja Terhadap Pekerja Disabilitas - Hennigusnia Hennigusnia (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2017)
One barrier for people with disabilities to obtain employment is negative perceptions of employers. As a result, many disabled people are underemployed. However, a small proportion of employers are willing to employ persons with disabilities. This paper presents the views of employers who employ workers with disabilities from some employers who employ disability workers. Semi-structured interviews that lasted for one and a half hours were conducted with five employers from service sectors. The Findings showed that the employers did recognize persons with disabilities as workers. The views of employers against workers were focused on the strengths and weaknesses in terms of personality and employee skills.The strengths of youth workers with disabilities in personality are hardworking, responsible, compliant, honest, and social ability. However, workers withdisabilities have low self-confident, and are very sensitive, and easily influenced by negative elements. The employers realized that the youth workers with disabilities did master the basic work skills that fulfilled the employers' needs. Nevertheless, they needed monitoring while working and repeated learning process if new training was given to them. This pioneer study is expected to provide significant contribution in employment implications to people with disabilities, and to reduce negative perceptions among employers in Indonesia.